Maria Manrique de Lara the Younger and Charles of Liechtenstein, or a love affair with financial benefits (Theatrum historiae, 2023)
Economic relations within the nobility at the turn of the 16th and 17th centuries were highly interconnected. We very often come across expressions of love that did not avoid the economic sphere either. Charles of Liechtenstein and Maria Manrique were a prime example of a loving couple with an economic overlap.
Keywords: economy; money; 16th century; 17th century; Charles of Liechtenstein; Maria Manrique de Lara